2020
DOI: 10.1177/2333794x20973146
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the BSID-II and the Bayley-III for Early School Age Cognitive Function in Very Preterm Infants

Abstract: Objective: To compare the predictive validity of the Bayley Scales of Infant Development, Second Edition (BSID-II) and the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III) for cognitive function at early school age in very preterm infants. Methods: Seventy-seven former preterm infants (born <32 weeks gestation and ≤2000 g) completed both the BSID-II and the Bayley-III at 2 years corrected age. Children enrolled at hospitals that perform follow-up beyond 2 years had cognitive asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…As confirmed by our findings, this risk is low when applying the BSID-II, as only one single child scored as ‘normal’ on MDI at the age of two years and ‘critical’ three years later. Altogether we interpret our results with Flynn et al (2020) “that the older BSID-II may actually be more predictive of later cognitive function than the Bayley-III” 70 . The younger the children are, the more combined developmental variables – as given in the BSDI-II – are indicative of cognition 40 .…”
Section: Discussionsupporting
confidence: 90%
“…As confirmed by our findings, this risk is low when applying the BSID-II, as only one single child scored as ‘normal’ on MDI at the age of two years and ‘critical’ three years later. Altogether we interpret our results with Flynn et al (2020) “that the older BSID-II may actually be more predictive of later cognitive function than the Bayley-III” 70 . The younger the children are, the more combined developmental variables – as given in the BSDI-II – are indicative of cognition 40 .…”
Section: Discussionsupporting
confidence: 90%
“…Although we also demonstrated that infants born at 24-25 weeks' gestation have delays in measures of brain development (FA and MD) compared to infants 26-27 weeks' gestation at birth, these structural changes were not linked to any significant changes in BSID-III scores at 2 years of age. It is possible that as BSID-III scores may overestimate neurodevelopmental scores, thus our analysis may have missed an association between DTI measures and infants with some level of NDI not identified by BSID-III testing [87][88][89].…”
Section: Discussionmentioning
confidence: 99%
“…Studying the outcome of preterm infants remains critical to enable early identification of high-risk children and to provide appropriate support (2,17,38). BSID-III is a widely used measure to study neurodevelopmental outcome in preterm infants (20). In contrast to other studies, BSID-III scores in our cohort were comparable with scores in term born children (38,39).…”
Section: Discussionmentioning
confidence: 61%
“…The (20,21) and a multidisciplinary risk evaluation for autism spectrum disorder (ASD) according to DSM-5 criteria (binarized as no risk (0) versus risk ( 1)) (22). The EF assessment took 15 minutes and was performed in the context of a global developmental assessment during the regular follow up of these children.…”
Section: Participantsmentioning
confidence: 99%